Tantangan dan Strategi untuk Meminimalisir Pelanggaran Kampanye Pilkada - Wiredarme Wiredarme; M. Zaenul Muttaqin (CV. Social Politic Genius (SIGn), 2022)
This study aims to analyze the regulation on challenges and strategies to minimize campaign violations of the Regional Head Election simultaneously in 2020 during the Covid-19 pandemic. The research method used is normative juridical. Data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal materials were then analyzed using qualitative data analysis methods. The results show that Law No. 6 of 2020, Regulation of General Election Commission No. 5 of 2020, Regulation of General Election Commission No. 13 of 2020, and Regulation of Election Supervisory Board No. 4 of 2020 has not been able to address the various violations of the 2020 Regional Head Elections campaign during the Covid-19 pandemic. In this case, mass mobilization exceeds the amount determined based on Regulation of General Election Commission No. 13 of 2020. In addition, the massive role of political buzzers indicates that money politics is rarely absent during the Regional Head Election campaign. Therefore, it is recommended to establish special regulations for pandemic situations, including prohibiting donations or other money politics. Furthermore, the involvement of political buzzers in online media who often use anonymous accounts requires specific regulations, including account legalization, content configuration, and content narrative. In addition, the application of health protocols in the Regional Head Election campaign should be based on Law No. 6 of 2018, which contains strict sanctions for violators of health protocols. From these recommendations, it is hoped that it will minimize the campaign violations of the Regional Head Election simultaneously in the future.